Some thoughts on qualitative research in psychology in Europe. Issue 3 (3rd July 2019) - Murray, Michael
ABSTRACT: This short commentary reflects upon some of the current debates about qualitative methods within European psychology. It notes that the rebirth of qualitative methods towards the end of the twentieth century often coupled an epistemological challenge to the quantitative orthodoxy within psychology with a political challenge to social injustice. However, more recently there have been tensions imposed by the increasing state and institutional surveillance of research. Qualitative researchers need to reflect upon these wider pressures if they are to retain their original critical impulse.